Urban governance dispositifs: cohering diverse ecologies of urban energy governance. (June 2021) - McGuirk, Pauline; Dowling, Robyn
As cities confront increasingly complex governance problems, conceptions of urban governance are becoming progressively more receptive to grasping its dynamic and multiplex nature, its connection to multiple lines of authority and forms of power, and the socio-material assemblages through which it works. Yet, despite conceptual advances around the dynamism and heterogeneity of urban governing assemblages and their durability, much remains to be understood about the processes and devices that compose and cohere their constituent elements to generate governance capacity. We explore this limitation by deploying Foucault's concept of 'dispositif' to analytically characterize how urban governance capacity is achieved around complex urban problems via processes and devices of composition and cohering. We do so by examining an emergent urban energy governance dispositif focused around top-tier commercial office space in Sydney, Australia: a key site around which multiple elements have been composed in a complex, entangled dispositif to produce effective urban governance capacity and accomplish substantive gains in office building energy performance. We characterise the socio-material elements involved and, more particularly, identify and analyse the processes and devices that compose the dispositif and cohere its governance capacity and we draw out the diverse forms of power that are immanent in these processes. These are, we argue, key steps in refining systematic understandings of the contemporary functioning and politics of the distributed urban governance of complex urban challenges. We conclude with key observations suggested by our analysis for urban governance scholarship.